2012
DOI: 10.3724/sp.j.1005.2012.01064
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics and gene mapping of a palea degradation(<I>pd2</I>) mutant in rice

Abstract: The yield and quality of rice are directly impacted by floral organ development in rice. Understanding of the floral development mechanism will be useful in genetic improvement of yield and quality. In this study, a rice mutant palea degradation 2 (pd2) in an indica cultivar '8PW33' was obtained after 60Co γ-ray treatment. Analysis of the mutant showed that, compared to the wild type, plant height, total grain number per panicle, and sword leaf width were significantly increased, but the seed setting rate were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…LIP1 and LIP2 genes are members of the AP2-like genes in A. majus, which is also involved in determining floral organ identities (Keck et al 2003). In rice, the DL gene (Yamaguchi et al 2004), PAL1 (Luo et al 2005), SL1 (Xiao et al 2009) and REP1, SDP1 or DP2 (Yuan et al 2009;Jin et al 2011;Yang et al 2012) have been identified as genes involved in floral development, but they do not belong to either the MADS-box nor AP2 gene families in rice. These results imply that a non-ABC-class gene may specify rice palea/lemma identity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…LIP1 and LIP2 genes are members of the AP2-like genes in A. majus, which is also involved in determining floral organ identities (Keck et al 2003). In rice, the DL gene (Yamaguchi et al 2004), PAL1 (Luo et al 2005), SL1 (Xiao et al 2009) and REP1, SDP1 or DP2 (Yuan et al 2009;Jin et al 2011;Yang et al 2012) have been identified as genes involved in floral development, but they do not belong to either the MADS-box nor AP2 gene families in rice. These results imply that a non-ABC-class gene may specify rice palea/lemma identity.…”
Section: Discussionmentioning
confidence: 99%
“…2011; Yang et al . 2012) have been identified as genes involved in floral development, but they do not belong to either the MADS-box nor AP2 gene families in rice. These results imply that a non-ABC-class gene may specify rice palea/lemma identity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations